Anatomy of the hyoid bone in camel (Camelus dromedarius) - JAIN, R K; KUMAR, PAWAN; GUPTA, A N (The Indian Journal of Animal Sciences, 2025)
The hyoid bone of camel consisted ofa body (basihyoideum) and 4 pairs of cornua. viz. thyroid cornu (thyrohyoideurn), small cornu (ceratohyoideum), middle cornu (epihyoideum) and great cornu (stylohyoideum). The basihyoideum had no lingual process, however, a small tubercle was observed in place of lingual process. The stylohyoideum was the largest and the longest while the epihyoideum and thyrohyoideum were almost of the same length. The ceratohyoideum was the smallest.